BECOMING MALAY: USE OF MALAY AND DUTCH LOANWORDS IN ARABIC CORRESPONDENCES OF THE ARABS IN THE 19TH CENTURY INDONESIA - Saifuddin Ahmad Husin (Universitas Islam Negeri Raden Fatah Palembang, 2021)
For at least hundreds of years Arab travelers and merchants, especially those originating from Hadhramaut, have had special relationship with Southeast Asia and its people. Historically this relationship has been very deep and permanent; sociologically extensive and continuous; and culturally heavy manifesting in various significant, and influential ways. One such influence is the adoption of many Arabic elements in the languages used in Indonesia. On the contrary, the Arabic language used by the Hadhramis in the archipelago was also influenced by Malayo-Indonesian language. This study aims to describe such use of loan words from Malay and Dutch in the Arabic language of the Hadhramis. The present study is data oriented. Some twenty-five copies of letters written in Arabic by the Hadhramis are analyzed. A closer look at the letters or correspondences from and to Hadhramaut and the Indonesian archipelago revealed that some Malay and Dutch lexicons were also used in their correspondences which were written in Arabic. Such use may indicate at least two aspects, socio-linguistic and socio-political. At the socio-linguistic aspect, the use of Malay and Dutch elements can be said as early process of bilingualism and adoption of new linguistic identity, while at the socio-political level such use shows how the beginning of the identification and adoption of new local or national identity.